Pengaruh Praktik Total Quality Management terhadap Internal Knowledge Transfer - Firman, Firman (TINGKAP, 2011)
ABSTRACT Total Quality Management (TQM) is a management philosophy of most organizations to improve the effectiveness and performance to become a world-class organization. The purpose of this study, using multiple regression analysis, was to test the effect of TQM practices of teamwork, autonomy, and process control on internal knowledge transfer. The results of this study with sample size is 85 faculty and high school leaders in Yogyakarta show that teamwork, autonomy, and process control has a positive effect on internal knowledge transfer. Kata Kunci: Total Quality Management (TQM), internal knowledge transfer